Hypertension and global DNA methylation: a population-based study in rural, Punjab, India - Anshika Kaushik; Debashis Bhattacharjee; Vineet Chaudhary; Suresh Dahal; Naorem Kiranmala Devi; R. P. Mitra; Rajinder K. Dhamija; Kewal Krishan; Ranjita Pandey; Kallur Nava Saraswathy (Scientific Reports)
Abstract Hypertension is a significant public health concern and a modifiable risk factor for increased mortality worldwide. It is reported to be influenced by gene-environment interactions and micronutrient intake. This study aims to understand the relationship between global DNA methylation levels and hypertension, independently and in the context of micronutrient status, among rural population in Punjab, India. A total of 2300 individuals, aged 30–75 years, (54.9% females) were screened for blood pressure. Of 2300 screened individuals, 900 (age sex matched 450 cases and 450 controls of hypertension) individuals were selected to examine the relationship between hypertension, global DNA methylation (5mC), and biochemicals (Folate, Vitamin B12, and Homocysteine). Folate, vitamin B12, and homocysteine levels were estimated using chemiluminescence technique. The ELISA-based colorimetric technique was used for performing peripheral blood leucocyte (PBL) global DNA methylation (5mC). Statistical analyses were performed using SPSS version 22.0. Hypertensives were found to have significantly lower levels of global DNA methylation than normotensives (0.65 vs. 0.72 respectively; p-value = 0.01*). Individuals in the 1st quartile of 5mC were at significantly (OR: 1.671; 95% CI: 1.206–2.315; p-value = 0.01*) increased risk for hypertension in comparison to those in the 4th quartile (reference). Further hypertensives on medication with controlled blood pressure (BP) were significantly hypermethylated as compared to hypertensives on medication with uncontrolled BP (0.70 vs. 0.62 respectively; p-value = 0.04*). Folate appeared to mediate global DNA methylation among hypertensives on medication-controlled BP. Further hypertension driven hypomethylation hints towards accelerated biological aging among younger hypertensives. Hypertension may be associated with Global DNA hypomethylation in the studied rural population of Punjab, India. Folate sufficiency may prove to be an aid in improving the methylation levels among the cases of hypertension who were on medication and had controlled BP.